Hongos patogenos en plantas ornamentales de importancia para Cuba - Perez Bocourt, Y.=700 1 Gomez Izaguirre, G.; Gonzalez Garcia, M.
(Es, En)
Ilus., 41 ref.
Keywords: PLANTAS ORNAMENTALES; HONGOS; ORGANISMOS PATOGENOS; PATOGENOS; CUBA